Images from the memory of the Inca and Ayutthaya Empires in contemporary novels:: a case study of The House of Mayura and The Deep Rivers - ลือสกุล, ภาสุรี (Journal of Letters, 2019)
This article analyses the construction of images from the memory of the Inca Empire in Peru and the Ayutthaya Empire in Thailand presented in contemporary fiction. It focuses on The Deep Rivers (Los Ríos Profundos, 1958), the neoindigenist novel of José María Arguedas, and The House of Mayura (1995), the historical fantasy novel of Kaew Kao. Both works narrate the protagonists’ journey between the past and present, and supernatural phenomena that the writers imagined based on local beliefs in Peruvian and Thai societies. While The Deep Rivers portrays the Incan capital Cusco, the The House of Mayura the city of Ayutthaya. This research is based on theories concerning memory and the fiction of memory, parallelism between the Inca and Ayutthaya Empires, their historical documents that reflect nostalgic perspectives, and the images of Cusco and Ayutthaya in Peruvian indigenist novels and Thai historical novels.